2015
DOI: 10.32674/jis.v5i2.428
|View full text |Cite
|
Sign up to set email alerts
|

The Factors That Influence Dietary Habits Among International Students in the United States

Abstract: This study examines the dietary intake changes and factors related to dietary acculturation in international students attending an urban university in the United States. The researchers administered seven focus groups of college-age international students (n = 32) between June and August 2012. The participants were enrolled in Northeastern and Midwestern U.S. universities. A qualitative research inquiry was used for data collection, presentation, and analysis. An interview guide was developed to explore the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…The present photovoice study is a good supplement to the current literature on culture and food choices as it provides some insights that were previously ignored in the literature. Although past literature recognizes the power of culture, most of them only focused on food shock and altered meal patterns (Gordon-Larsen et al, 2003;Lara et al, 2005;McDonald and Kennedy, 2005;Alakaam et al, 2015). Our findings highlight the important role of food in contributing to the attainment of belonging for international students.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The present photovoice study is a good supplement to the current literature on culture and food choices as it provides some insights that were previously ignored in the literature. Although past literature recognizes the power of culture, most of them only focused on food shock and altered meal patterns (Gordon-Larsen et al, 2003;Lara et al, 2005;McDonald and Kennedy, 2005;Alakaam et al, 2015). Our findings highlight the important role of food in contributing to the attainment of belonging for international students.…”
Section: Discussionmentioning
confidence: 52%
“…Many scholars have addressed how the challenges to adapt to the new culture affects food consumption. To clarify, the transition to a new culture has negative effects on health and diet, such as altered dietary patterns, higher alcohol intake, weight gain, increased blood glucose levels, high blood pressure, and mental problems (Gordon-Larsen et al, 2003;Lara et al, 2005;McDonald and Kennedy, 2005;Alakaam et al, 2015). Research on dietary practices of international students found that international students consume more salty, sugary fast foods, and fewer fruits and vegetables after staying in the U.S. (Wu and Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, there were no meaningful changes, indicating other factors influencing one's decision to change their dietary habits despite having adequate knowledge. A previous study [31] identified three main factors that took parts in determining one's ability to adopt healthy diet and eating habits. Those three are food environment, individual preferences, and religious influences [31].…”
Section: Discussionmentioning
confidence: 99%